Growth of Maize (Zea mays L.) Under Cadmium Sulfate (CdSO4) Heavy Metal Stress - Mukarlina Mukarlina; Irwan Lovadi; Widdiya Ariyani (Jurnal Biologi Tropis, 2026)
Cadmium (Cd) is a heavy metal soil pollutant that can be toxic to plants. This study investigated the response of maize (Zea mays L.) grown in peat soil exposed to different levels of Cd stress. Four concentrations of CdSO₄ (0, 20, 40, and 60 ppm) were applied using a completely randomized design with three replications. Growth performance was evaluated through plant height, leaf production, and fresh biomass, while Cd accumulation in plant tissues was determined using Atomic Absorption Spectrophotometry (AAS). The results showed that the application of heavy metal cadmium sulfate (CdSO4) in the planting media up to 60 ppm did not affect the plant height, number of leaves and wet weight of maize. Maize showed tolerance to cadmium stress, as the application of CdSO₄ up to 60 ppm. Cadmium was detected in both roots and shoots, with greater accumulation occurring in the roots. This pattern suggests that maize restricted Cd movement to aerial tissues, which may contribute to its tolerance under Cd exposure. The findings indicate that maize can maintain normal vegetative growth under moderate Cd stress in peat soil. Further research is needed to assess long-term effects and cadmium accumulation in plant tissues.